2013
DOI: 10.3329/bjch.v36i3.14272
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double Blind Trial to Compare the Efficacy of Granisetron And Ondansetron in Controlling Emesis in Children with Acute Lymphoblastic Leukemia

Abstract: Methods: In this randomized double blind trial 60 children (4-11 years) with acute lymphoblastic leukemia (ALL) who received high dose methotrexate (HDMTX-2.5gm/ m 2) . Each patients received either ondansetron 4 mg or granisetron 1mg (n=30) orally half an hour before HDMTX. Nausea and vomiting were assessed based on ''modified Morrow Assessment of Nausea and Emesis'' (MANE) scale for application to the children. Results: Complete response of granisetron significantly differed from ondansetron from day 2-4 (de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A double-blind, randomized study by Siddique et al reported that complete and partial responses to CINV in ondansetron administration alone were 70% and 30%, respectively, for the acute type, and 43% and 50%, respectively, for the delayed type. 31 Jaing et al reported that administration of 0.15 mg/kg ondansetron gave a complete response of 45.5%. 7 In addition, Holdsworth et al reported that complete response to ondansetron (0.45 mg/kg IV) was seen in 65.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A double-blind, randomized study by Siddique et al reported that complete and partial responses to CINV in ondansetron administration alone were 70% and 30%, respectively, for the acute type, and 43% and 50%, respectively, for the delayed type. 31 Jaing et al reported that administration of 0.15 mg/kg ondansetron gave a complete response of 45.5%. 7 In addition, Holdsworth et al reported that complete response to ondansetron (0.45 mg/kg IV) was seen in 65.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…It corresponds to Siddique R et al, who observed nausea in 36.6% of children's (4-10 years) within 48 hours of HD-MTX infusion. [12] Another study with reference to Vaishnavi K et al, who observed vomiting in 53% patients younger than 15 years. [8] It also corresponds to the study of Rask C et al, who observed nausea/vomiting in 28.25 of patients.…”
Section: Population Descriptionmentioning
confidence: 97%